Mixture design approach for the development of a cowpea and banane cochon flour-based gluten-free biscuit: Chemical, glycemic load, sensory and microbiological characteristics of the optimal biscuit - Bilkissou Njapndounke; Romial Joel Ngouénam; Edith Marius Foko Kouam; Gires Teboukeu Boungo; Julie Mathilde Klang; François Zambou Ngoufack (Future Foods, 2023)
This research aimed to formulate a protein-enriched, low lipid, low reducing sugar gluten-free biscuit from blend flour of Vigna unguiculata (cowpea) and Musa sapientum (banane cochon) which was safe for consumption and had an acceptable glycemic load. Five blend flours from banane cochon and cowpea were generated using mixture design. The former were evaluated for their pasting and physicochemical properties. Also, the numerical optimization technique was used to predict the desired protein, lipid and reducing sugar contents of the biscuit. This was followed by the evaluation of the nutritional, sensory, microbial stability and glycemic load of the optimal biscuit. This study revealed a significant (p < 0.05) difference in the pasting and nutritional properties of the blend flours. When it comes to optimization of the blend flour proportion for biscuit production, the appropriate flour ratio was 79.42 % (banane cochon flour) and 20.59 % (cowpea flour). This gave an optimal gluten-free biscuit with protein content that increased from 6.8 % to 11.64 %, while the lipid and reducing sugar content were maintained at a low amount of 18.73 % and 12.33 % respectively. The formulated product had a glycemic load of 18.9, acceptability score of 7.18 and was microbiologically safe for consumption for three months.